Service learning with First Peoples: a framework to support respectful and reciprocal learning - Bartleet, B.; Bennett, Dawn; Power, A.; Sunderland, N. (Routledge, 2019)
This article outlines a framework for working with First Peoples. The framework supports respectful and mutually beneficial learning partnerships and culminates from 6 years of practice and research in arts-based service learning with Aboriginal communities in Australia. We begin by looking at synergies between global service learning and service learning with First Peoples. We then position this work within an international context, focusing on Indigenous frameworks for practice identified in service learning with First Nations communities in North America. We next describe the Australian context and touch on the multilayered intercultural processes and outcomes associated with the programmes across three universities. Finally, we introduce the framework and elaborate on its dimensions.